An efficient synthesis of iminoisoindolione derivatives by cobalt-catalyzed oxidative isocyanide insertion - Zou, Feihua; Chen, Xuwen; Hao, Wenyan (Tetrahedron, 2017)
A Cobalt-catalyzed oxidative isocyanide insertion of aminoquinoline benzamides has been developed. The reaction proceeded smoothly by using Ag2CO3 as the oxidant in PhCl at 120 °C and delivered products in moderate to excellent yields with excellent functional group tolerance. The transformation is supposed to undergo the ortho CH activation and isocyanide insertion of CCo species toward the benzamides. Attractive features of this system include the use of low cost cobalt catalyst, the easyhandling operation, and readily available substrates. [Display omitted] •A cobalt-catalyzed oxidative isocyanide insertion involving CH bond activation is reported.•The reaction generates a variety of iminoisoindoliones in good yields.•Isocyanide as a C1 source inserted into two nucleaphlies can construct heterocycle.